Investigation of the triad women's athlete components in gymnasts - DOI: 10.4025/reveducfis.v20i2.5677 - Talita Adão Perini; Glauber Lameira de Oliveira; Paulo Moreira Silva Dantas; Paula Roquetti Fernandes; José Fernandes Filho (Revista da Educação Física)
The purpose of this study was to investigate the presence of the Triad Women's Athlete Syndrome (TWA) components, as well as the satisfaction with the self-body image was checked in gymnasts, comparing it with non-athlete teenage women. The sample was made of 29 female adolescent professional gymnasts [15,0 ± 2,8 years], and 32 non-athletes [15,0 ± 1,6 years]. Three self-image validated questionnaires were used: 1st - Anamnesis - general and nutritional information, training routine and period cycle; 2nd - Eating Attitudes Test - presence of inappropriate eating, with risk of TA development; and 3rd - Body Shape Questionnaire - identification of the self-body image distortion degree. The satisfaction with the self-body image was checked, by the difference of total body mass, which was measured by the evaluators and declared as ideal by them. Body measurements were taken from every individual of the sample, using the ISAK international standardization. For the data analysis, the Microsoft Excel 2000 Software was used, using p ≤ 0,05. The study demonstrated that every evaluated women, form both groups, showed no TWA. But in one gymnast (3,4%), the presence of two of these components was noticed simultaneously, and in fifteen of them (51,7%), a single component, either TWA, period disorder, or osteoporosis. It is concluded that gymnastics can be considered a risk for the development of TWA components, making the gymnast vulnerable in at least one of three components that characterize the TWA.